One Hundred Thousand Whys: A Classic in Chinese Book History. Issue 5 (October 2018) - Wang, Guoyan; Du, Junfei
One Hundred Thousand Whys is a widely known popular science book in China, which has been developing people's systematic understanding of basic sciences for generations. This encyclopedic book covers a wide range of topics, inspiring people's observations and pondering about the world by asking nonspecialist questions. Different questions are raised and followed by answers that satisfy readers' scientific curiosity; cultivate the scientific literacy of generations of children, and even of adults; and make up for the shortcomings of scientific education in China's schools. In the past half-century, it has become a legend and classic in Chinese publishing history.